2019
DOI: 10.1038/s41598-019-50695-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel miRNA-4484 is up-regulated on microarray and associated with increased MMP-21 expression in serum of systemic sclerosis patients

Abstract: Systemic sclerosis (SSc) is a complex, heterogeneous connective tissue disease, characterized by fibrosis and ECM deposition in skin and internal organs, autoimmunity, and changes in the microvasculature. Profiling of circulating miRNAs in serum has been found to be changed in pathological states, creating new possibilities for molecular diagnostics as blood-based biomarkers. This study was designed to identify miRNAs that are differentially expressed in SSc and might be potentially contributing to the disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…Matrix metalloproteinase-21 (MMP-21), even though not a direct target gene according to computational analysis, was hypothesized to be up-regulated by miR-4484 due to their close chromosomal vicinity and the increased MMP-21 serum levels. These findings further enabled the authors to suggest that miR-4484 and MMP-21 might play a role in SSc pathogenesis and proposed them as serum biomarkers [45].…”
Section: Serum-and Tissue-specific Mirna Signatures In Sscmentioning
confidence: 87%
See 3 more Smart Citations
“…Matrix metalloproteinase-21 (MMP-21), even though not a direct target gene according to computational analysis, was hypothesized to be up-regulated by miR-4484 due to their close chromosomal vicinity and the increased MMP-21 serum levels. These findings further enabled the authors to suggest that miR-4484 and MMP-21 might play a role in SSc pathogenesis and proposed them as serum biomarkers [45].…”
Section: Serum-and Tissue-specific Mirna Signatures In Sscmentioning
confidence: 87%
“…A different miRNA circulating profile was demonstrated by means of microarray analysis in the serum of 10 SSc patients compared to six HC in a study by Rusek et al (2019). Out of the 15 miRNAs differentially expressed, miR-4484 was remarkably increased (18-fold).…”
Section: Serum-and Tissue-specific Mirna Signatures In Sscmentioning
confidence: 98%
See 2 more Smart Citations
“…Clinical studies show that miRNAs expression profiles in cell-free serum from patients with different autoimmune diseases, including SSc, systemic lupus erythematosus, rheumatoid arthritis, and mixed connective disease [ 140 ]. For instance, Rusek et al have reported an upregulation of novel serum miRNA-4484 associated with increased MMP-21 expression in SSc [ 141 ]. Furthermore, Chouri et al have reported that miRNA-483-5p in serum is a potential driver of fibrosis in SSc [ 142 ].…”
Section: Lncrnas As Biomarkers For Diagnosis Prognosis and As Targets For Gene Therapymentioning
confidence: 99%